1990
DOI: 10.1159/000138644
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Cigarette Smoking on Antipyrine Oxidation versus Acetaminophen Conjugation

Abstract: The effect of cigarette smoking on drug oxidation and conjugation was studied using antipyrine and acetaminophen as marker compounds. For the antipyrine study, healthy cigarette smokers (n = 30) and nonsmoking controls (n = 53) received a single 1.0-gram intravenous dose of antipyrine. For the acetaminophen study, 14 smokers and 15 nonsmokers received a 650-mg intravenous dose of acetaminophen. The clearance of antipyrine was significantly increased (0.93 vs. 0.60 ml/min/kg, p < 0.0001) and elimination half-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…The degree of enhancement of N-acetyl-p-benzoquinone imine formation is similar to that which we observed for acetaminophen glucuronidation (less than 2-fold), but may occur more rapidly since the primary mechanism of induction of CYP2E1 is post-translational (Thummel et al, 2000). In good agreement with the results of the present study, cigarette smoking was previously shown in two different studies (Scavone et al, 1990;Miners and Mackenzie, 1991) to have no effect on acetaminophen conjugation in vivo. In contrast, the results of a third study suggested that heavy smoking (Ͼ40 cigarettes per day) was associated with higher urinary acetaminophen glucuronide excretion (Bock et al, 1987).…”
Section: Ugt1a6 Pharmacogenetics 1337supporting
confidence: 91%
“…The degree of enhancement of N-acetyl-p-benzoquinone imine formation is similar to that which we observed for acetaminophen glucuronidation (less than 2-fold), but may occur more rapidly since the primary mechanism of induction of CYP2E1 is post-translational (Thummel et al, 2000). In good agreement with the results of the present study, cigarette smoking was previously shown in two different studies (Scavone et al, 1990;Miners and Mackenzie, 1991) to have no effect on acetaminophen conjugation in vivo. In contrast, the results of a third study suggested that heavy smoking (Ͼ40 cigarettes per day) was associated with higher urinary acetaminophen glucuronide excretion (Bock et al, 1987).…”
Section: Ugt1a6 Pharmacogenetics 1337supporting
confidence: 91%
“…Results from several in vivo studies suggest that the clearance of acetaminophen (Bock et al, 1994; Bock et al, 1987), oxazepam (Ochs et al, 1981), and codeine (Yue et al, 1989; Yue et al, 1994) is higher in cigarette smokers, although the extent of the difference was small and probably clinically unimportant. In contrast, results of several other studies show no effects of smoking on the clearance by glucuronidation of acetaminophen (Miners et al, 1984; Scavone et al, 1990), diflunisal (Macdonald et al, 1990), and lorazepam (Ochs et al, 1985). …”
Section: Interindividual Variability In Activity Of the Major Ugt Isomentioning
confidence: 63%
“…Measuring of antipyrine clearance (plasma or saliva) makes it possible to explain interindividual and intra-individual variations drug response variations, which may be genetic 20 , secondary to a pathological situation 21 , a drug interaction 22 or related to exogenous factors, such as diet 23,24 , tobacco 25 , physical activity 26 and exposure to chemical substances 27 .…”
Section: Discussionmentioning
confidence: 99%